2018
DOI: 10.15640/ijgws.v6n1a5
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring for Female Academics in the 21st Century: A Case Study of a South African University

Abstract: This paper investigated the female academics" perceptions on mentoring in universities and how it can promote their career trajectory. The study adopted the qualitative methodology. Using evidence collected from a case study of a South African university and a sample size of purposively selected five senior female academics and a focus group of five junior female academics were used for the study. The research solicited data through interviews and document analysis. The results revealed that mentoring is there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The nding of this study agrees with the result of Okurame cited in Undiyaundeye and Basake (2017), that mentoring relationships are often useful to the senior partner in the union, as it provides an opportunity for them to develop a base for technical support and power. This nding corroborates the nding of Chitsamatanga et al (2018) that mentoring is there in universities theoretically, but the practical concept appears to be surrounded by grey areas. The cited study also showed a general lack of interest and knowledge among academics on mentoring and networking.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The nding of this study agrees with the result of Okurame cited in Undiyaundeye and Basake (2017), that mentoring relationships are often useful to the senior partner in the union, as it provides an opportunity for them to develop a base for technical support and power. This nding corroborates the nding of Chitsamatanga et al (2018) that mentoring is there in universities theoretically, but the practical concept appears to be surrounded by grey areas. The cited study also showed a general lack of interest and knowledge among academics on mentoring and networking.…”
Section: Discussionsupporting
confidence: 87%
“…The research of Chitsamatanga et al (2018) discovered that mentoring is there in universities theoretically, but the practical concept appears to be surrounded by grey areas. The study of the cited scholars revealed a myriad of problems surrounding mentorship such as a general lack of interest, knowledge and ignorance from the academics on mentoring and networking, academics' perceptions of mentoring and networking in universities, as well as a shortage of role models.…”
Section: Mentorship and Academic Staff Research Productivitymentioning
confidence: 99%
“…In the academic fraternity, there is a lack of support for mentorship required specifically for the emerging cohort of Black female academics (Chitsamatanga, Rembe, and Shumba 2018). This is evident from the skewed representation in universities where males dominate most of the senior academic positions.…”
Section: Constraints In Advancing Black Women Academicsmentioning
confidence: 99%
“…Nkumane (2018) found that there was a need for programmes to cater for academic researchers over 50 years of age in South African higher education. Overall, a lack of support, particularly for women, is prevalent in the universities and it is prudent to address this imbalance to ensure that women academics are advanced (Chitsamatanga et al 2018). Studies have shown that funding is seen as a challenge for the progression of the Black women academics.…”
Section: Constraints In Advancing Black Women Academicsmentioning
confidence: 99%
See 1 more Smart Citation